(untitled) (Acta Polytechnica CTU Proceedings, 2019)
46th Conference with international participation FOUNDATION ENGINEERING Title: Modern Technologies in Geotechnical Engineering The traditional yearly conference of Foundation Engineering Brno is organized by the Czech Geotechnical Society. This is the largest annual event in the field, where researches, academicians, designers, investors and contractors present, share and discuss the results of their research and share their experiences with each other. Each year is focused on a certain topical subject. Selected experts from abroad are invited for Keynote lecture for each conference. This issue of Acta Polytechnica Proceedings includes selected scientific papers that were presented at the 46th Conference of the Foundation Engineering held in Brno in 2018. The focus of this conference was Modern Technologies in Geotechnical Engineering. The scientific program was divided into five sections: • Geotechnical investigation • Earth structures • Foundation structures • Underground structures • Significant geotechnical structures realized in the Czech Republic and abroad Date: November 19.-20. 2018 Venue: Brno, Czech Republic URL: www.cgts.cz Organized by: Czech Geotechnical Society of the Czech Institution of Civil Engineers Guest editor: Daniel Jirásko Scientific comittee: Jana Frankovská (STU Bratislava, Slovak Republic) Eva Hrubešová (TU Ostrava, Czech Republic) Lubomír Klímek (Geotest a.s.) Mária Masarovičová (STU Bratislava, Slovak Republic) Jan Masopust (Czech Technical University in Prague, Czech Republic) Lumír Miča (Brno University of Technology) Petr Nosek (Foundation Engineering company, Czech Republic) Jindřich Řičica (EFFC, UK) Ivan Slávik (STU Bratislava, Slovak Republic) Petr Svoboda (Keller-Special Foundation) Peter Turček (STU Bratislava, Slovak Republic) Kamila Weiglová (Brno University of Technology, Czech Republic) Local organizing comittee: Ivan Vaníček Daniel Jirásko Josef Jettmar Jirí Barták Taťana Holoušová Michael Remeš Guarantor of the peer review proces: Daniel Jirásko Guarantor of language editing: Renáta Nivenová